Channel Measurements and Modeling at 6 GHz in the Tunnel Environments for 5G Wireless Systems. (10th December 2017) - Li, Shuang-de; Liu, Yuan-jian; Lin, Le-ke; Sheng, Zhong; Sun, Xiang-chen; Chen, Zhi-peng; Zhang, Xiao-jun
Abstract : Propagation measurements of wireless channels performed in the tunnel environments at 6 GHz are presented in this paper. Propagation characteristics are simulated and analyzed based on the method of shooting and bouncing ray tracing/image (SBR/IM). A good agreement is achieved between the measured results and simulated results, so the correctness of SBR/IM method has been validated. The measured results and simulated results are analyzed in terms of path loss models, received power, root mean square (RMS) delay spread, Ricean K-factor, and angle of arrival (AOA). The omnidirectional path loss models are characterized based on close-in (CI) free-space reference distance model and the alpha-beta-gamma (ABG) model. Path loss exponents (PLEs) are 1.50–1.74 in line-of-sight (LOS) scenarios and 2.18–2.20 in non-line-of-sight (NLOS) scenarios. Results show that CI model with the reference distance of 1 m provides more accuracy and stability in tunnel scenarios. The RMS delay spread values vary between 2.77 ns and 18.76 ns. Specially, the Poisson distribution best fits the measured data of RMS delay spreads for LOS scenarios and the Gaussian distribution best fits the measured data of RMS delay spreads for NLOS scenarios. Moreover, the normal distribution provides good fits to the Ricean K-factor. The analysis of the abovementioned results from channel measurements and simulations may be utilized for the design of wireless communications of future 5G radio systems at 6 GHz.